Experimental and numerical approaches to investigate the out-of-plane response of unreinforced masonry walls subjected to free far-field blasts. (15th July 2021) - Godio, Michele; Williams Portal, Natalie; Flansbjer, Mathias; Magnusson, Johan; Byggnevi, Magnus
Highlights: Experimental and numerical methods for the blast response of unreinforced masonry are reviewed. A synthetic analysis of the available literature is provided. For test methods, focus is on test setup, boundary conditions, failure mechanisms, measurements. For modelling strategies, level of detail and cost are included. Analysts are assisted in selecting suitable investigation tools for masonry subjected to blasts. Abstract: Masonry walls are bulky and heavy and have therefore the potential to act naturally as a protective system to blasts. Yet, they are known to have a limited flexural and torsional capacity, particularly when unreinforced. When exposed to shockwaves, they experience out-of-plane failure mechanisms which may affect the overall stability of the building and engender flying debris inside the building. The out-of-plane response of unreinforced masonry walls to blasts depends on many factors characterizing both the wall and blast action, making any sort of prediction difficult. In this context, experimental tests and numerical models become key tools that can be used to study the wall's response on a case-by-case basis. This review covers the major experimental and numerical approaches to assess the out-of-plane response of unreinforced masonry walls subjected to blasts. A methodological appraisal is used for the test methods, focusing on the preparation of the test items and test setup, the boundary conditions and failure mechanisms investigated, as well as the commonly employed measurement techniques. The survey on the modelling approaches includes key topics such as level of detail and cost, and reports strategies to model the wall and blast scenario. The review provides a thematic analysis of the available literature, aimed to assist the analyst in selecting a suitable tool for the investigation of masonry in the field of blast engineering. Furthermore, the findings presented herein can support amendments of existing codes and guidelines pertaining to the design of protective masonry structures.